Evidence from simulated climatic conditions indicates rising CO2 levels impact pearl millet yield and nutritional traits - Mahalingam Govindaraj; Ramanagouda Gaviyappanavar; Avijit Tarafdar; Raju Ghosh; Sean Mayes; Pooja Bhatnagar-Mathur; Mamta Sharma (Journal of Agriculture and Food Research)
Rising atmospheric CO2 significantly impacts crop productivity and nutritional quality, posing challenges to global food security. Pearl millet (Pennisetum glaucum (L.) R. Br.), a climate resilient nutri-cereal, plays a vital role in food and nutrition security particularly in arid and semi-arid regions of India and sub-Saharan African countries. However, its response to changing climate conditions such as elevated CO2 are not well known. This study assessed the response of various pearl millet genotypes, including hybrids and inbred lines to elevated CO2 (550 and 700 ppm) from the current level of 420 ppm. Elevated CO2 resulted in enhanced plant height, chlorophyll content, and nitrogen balance index. However, average grain yield recorded 1.2 % reduction at 550 ppm and 28.8 % at 700 ppm. Flavonoid concentration increased at 550 ppm (5.1 %) but decreased at 700 ppm (14.5 %). Average grain Fe and Zn content increased at 550 ppm by 4.25 % and 6.12 %, respectively but declined at 700 ppm by 4.01 % and 7.04 %; however in ICMB 92111, ICMB 92888, HHB67Imp and NBH 4903 increased Fe accumulation was recorded at 700 ppm) Grain protein content decreased significantly (1.12 % at 550 ppm, 13.4 % at 700 ppm), while fodder protein increased (16.01 % at 550 ppm, 15.19 % at 700 ppm). These findings highlight the complex effects of CO2 fertilization on pearl millet's productivity and nutritional profile; the crop remains relatively resilient up to 500 ppm CO2 but becomes more susceptible to negative impacts at 700 ppm. Therefore, large-scale germplasm evaluation and targeted breeding efforts are essential to develop climate-resilient genotypes with stable yields and enhanced nutrient content under future CO2 conditions.